Combined QSAR, molecular docking and molecular dynamics study on new Acetylcholinesterase and Butyrylcholinesterase inhibitors. (June 2018) - Daoud, Ismail; Melkemi, Nadjib; Salah, Toufik; Ghalem, Said
Graphical abstract: Highlights: Novel derivatives related to 4-[(diethylamino) methyl] -phenol was tested theirs inhibitory effects against AChE and BuChE. QSAR, Molecular Docking/Dynamics and ADME studies were used to find the best compounds with high affinity. Compound 23 and compound 28 showed the most potent anti-AChE and anti-BuChE activity respectively. Abstract: Background and purpose: This work deals with several molecular modeling methods used to discover new therapeutic agents for treating the Alzheimer's disease (AD). The cholinergic hypothesis was initially presented over 30 years ago and suggests that a dysfunction of acetylcholine containing neurons in the brain. Acetylcholinesterase (AChE) and Butyrylcholinesterase (BuChE) are of the keys targets of drugs for treating AD. Methods: QSAR, Molecular Docking/Dynamics and ADME properties were carried out in order to study 36 compounds that belong to the 4-[(diethylamino)methyl]-phenol derivatives and test their AChE and BuChE inhibitory activities, MOE, HyperChem and others softwares were used to find the best compounds with high affinity. Results: The QSAR models exhibited good statistical values for both targets AChE (R 2 adj  =  0.660, q 2  =  0.70, F-ratio =  18.008) and BuChE (R 2 adj  =  0.726, q 2  =  0.75, F-ratio =  31.864) . The interactions between the studied inhibitors and our targets were further explored through molecular docking and molecular dynamics simulations. A few key residues (TRP279, TYR334, PHE330 and TRP84) at the binding site of AChE and key residues (HIS438, TYR332, PHE329 and TRP82) at the binding site of BuChE were identified. Conclusion: Based on this study compounds 23 and 28 have no violated Lipinski's rule of five and thus, showing the possibility of being potential candidates for further studies in drug development process against the AChE and BuChE targets respectively.